ISI Bibliometric profile of Universidad de Concepción School of Dentistry, 1989-2012. - Javier Moraga; Alex Zúñiga (Universidad de Concepción., 2013)
Aim: To characterize personal, institutional or national scientific production is a need to understand and improve the generation of knowledge. The aim of this study is to describe the bibliometric profile of ISI publications related of Universidad de Concepción School of Dentistry during 1989-2012 timespan.Matherial and methods: Bibliometric study. A search on Web of Knowledge of Thomson Reuters for Science Citation Index Expanded database was perfomed, about the scientific productivity of Universidad de Concepción School of Dentistry during 1989-2012 period. The analyzed variables were the number of publications, cites, magazines on which they were published, authors, institutions and coauthor countries.Results: Thirty nine articles were identified. These articles were cited in 266 opportunities (6,82 cites per article and h-index of 10). In relation with journals, stands out Oral Surgery Oral Medicine Oral Pathology Oral Radiology and Endodontology (21.9%), Journal of Oral Pathology Medicine (12.2%), and International Journal of Morphology (7.3%). More productive authors were Rojas (13), Martínez (11) y Brethauer (9). 48,72% of publications was concentrated in last five-years and 69.23% in last ten-years.Conclusions: Universidad de Concepción School of Dentistry scientific production is poor, being observed an increase during the last 5 years.